Ebola-Associated Terms in Hausa, Igbo and Yoruba. (2016)
The West African Ebola outbreak of 2014 was declared a public health emergency of international concern under the International Health Regulations by the World Health Organisation (WHO) Director General. In spite of the devastating nature of Ebola, many Nigerians do not have access to information on the disease in the language they understand best. This study therefore translates Ebola-associated terms into Nigeria’s three major languages (i.e. Hausa, Igbo and Yoruba) with a view to making information on Ebola accessible to the grassroots population. It also embarked on a survey of 9 purposively selected states where the major languages are predominantly spoken as L1 in order to determine the level of stakeholders’ familiarity with Ebola as well as their opinions on the need for Ebola-associated lexicon in Nigerian indigenous languages.